2016
DOI: 10.1159/000444704
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Treatment of Pain after Hip Fracture in Elderly Patients with Dementia

Abstract: Background/Aims: Prior studies have shown that patients with dementia are at risk of receiving insufficient treatment for pain after a hip fracture. We therefore hypothesized that elderly hip fracture patients with dementia received less postoperative pain treatment than those without dementia. Method: All patients (age ≥65 years) who had been operated on for a hip fracture in the Copenhagen University Hospital region in 2009 were included. Data about analgesic use for the first 72 h after surgery were acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 42 publications
(50 reference statements)
2
53
1
Order By: Relevance
“…Capability and willingness to care for patients with dementia is increasingly a general competency requirement for orthopaedic nurses. A Danish study demonstrated that 19% of all patients admitted to an orthopaedic ward either had a dementia diagnosis or were receiving dementia‐related medications (Jensen‐Dahm et al, ). In addition, a large number of hospitalised acute care patients are known to either be undiagnosed or experience drug‐induced delirium (Reynish et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Capability and willingness to care for patients with dementia is increasingly a general competency requirement for orthopaedic nurses. A Danish study demonstrated that 19% of all patients admitted to an orthopaedic ward either had a dementia diagnosis or were receiving dementia‐related medications (Jensen‐Dahm et al, ). In addition, a large number of hospitalised acute care patients are known to either be undiagnosed or experience drug‐induced delirium (Reynish et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that as many as 42% of patients can be expected to have dementia with only half diagnosed with dementia prior to admission (Sampson, Blanchard, Jones, Tookman, & King, ). A Danish study investigated all hospital admissions for a column fracture of the femur over the course of a year and revealed 19.2% of the admissions either had a diagnosis of Alzheimer disease or received a medication from the NO6 psychoanaleptics (NO psychoanaleptics, ) group of drugs for the management of dementia symptoms (Jensen‐Dahm, Palm, Gasse, Dahl, & Waldemar, ). People with dementia are three times more likely than other citizens to be hospitalised for hip fracture (Baker, Cook, Arrighi, & Bullock, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to do so may result in a denial of appropriate medication or therapeutic intervention, prescription of analgesics at inadequate dosages, or use of inappropriate medication (e.g., antipsychotics) [15-20]. These may lead to poor quality of life and premature death in these individuals [21-25].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies indicate more frequent use of paracetamol, but less frequent use of nonsteroidal antiinflammatory drugs (NSAIDs) among community dwellers with cognitive disorders compared to other older adults [11,12]. Reports on opioid use have been more inconsistent, but a higher prevalence of opioid use, strong opioid use, and long-term opioid use have also been found among persons with cognitive disorders compared to those without [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%